Automatic Counting of Spodoptera litura（Lepidoptera: Noctuidae）Using a Pheromone Trap with a Photoelectric Sensor and Single-board Computer - Iwata, Daisuke; Kobayashi, Yutaka; Ishimoto, Masuhiro (Japanese Journal of Applied Entomology and Zoology, 2020)
To automate pheromone trap surveys at a low cost, we developed a new counting system equipped with a photoelectric sensor and single-board computer for Spodoptera litura Fabricius（Lepidoptera: Noctuidae）. We set a funnel trap with this system in a soybean field from August 14 to September 4 in 2018. As a result, the number of trap catches and the count obtained by the photoelectric sensor were positively correlated. However, the count obtained by the photoelectric sensor was significantly larger than the number of trap catches. To avoid counting the same individual multiple times, we corrected the numbers of the count obtained by the photoelectric sensor, if there was a count within a certain time from the previous count. Using this the correction, the automated counts of the trap catches were improved.